A new tuberculated Pristimantis (Anura, Terrarana, Strabomantidae) from the Venezuelan Andes, redescription of Pristimantis pleurostriatus, and variation within Pristimantis vanadisae - Barrio-Amorós, César L.; Heinicke, Matthew P.; Hedges, S. Blair (Zootaxa, 2013)
A new tuberculated Pristimantis is described from the eastern versant of the Venezuelan Andes. The new species is found in cloud forest at around 1600 masl on the eastern side of the Cordillera de Mérida. It is distinguished from other similar tuberculated species by its round, ill-defined canthus rostralis, ill-defined canthal stripe, and absence of pale spots on the groin and posterior surface of thighs. Pristimantis pleurostriatus is a poorly known species found in cloud forest on the western slopes of the Venezuelan Andes. We redescribe the species based on topotypic specimens. Pristimantis vanadisae is a polychomatic species varying dramatically in pattern; four chromotypes are described. Molecular data are presented which distinguish among tuberculated and other species of Pristimantis in the Cordillera de Merida. Molecular data also support placement of Mucubatrachus and Paramophrynella in Pristimantis.